ICERD in Malaysian online news reports: Analysis of rhetoric and public opinion - Nuurrianti Jalli; Siti Aeisha Joharry; Sabariah Mohamed Salleh (Social Sciences and Humanities Open, 2022)
In late 2018, the International Convention for the Elimination of Racial Discrimination (ICERD) became one of the most discussed issues in Malaysian cyberspace. To date, 179 countries in the world have ratified ICERD excluding Malaysia. This research examined the representation of ICERD in news reports of four English online newspapers in Malaysia - The Star Online, Malay Mail, Malaysiakini, and Free Malaysia Today. A corpus-assisted discourse analysis was firstly conducted to investigate how ICERD was depicted in these selected news portals from 15 November until December 15, 2018. Corpus analysis found that all English online news portals were inclined to represent ICERD in a negative light. Methodologically, this study has demonstrated the synergy of corpus techniques (CADS), illustrate the complexity of racial issues, especially ones related to the Malay group and how their opinions are closely associated with Islam.